THE EFFECT OF ADSORBENT TYPE AND RATIO ON REMOVAL AND ISOTHERM ADSORPTION OF METHYLENE BLUE - Lia Cundari; Eki Saputra; Agus Suranto; Yandriani Yandriani; Rosalina Rosalina (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2020)
THE EFFECT OF ADSORBENT TYPE AND RATIO ON REMOVAL AND ISOTHERM ADSORPTION OF METHYLENE BLUE. Methylene Blue (MB) is one of the dye that are widely used in the textile industry. The wastewater from textile industry that contain MB can reduce the oxygen level in water bodies. This study aims to determine the efficiency of the adsorbent in MB removal and to analyze the isotherm adsorption. The variations conducted in this research was the type of adsorbent and its ratio. The activated carbon that used as adsorbent was fresh betel nut (Cyrtostachys lakka) activated carbon (A), regenerated betel nut activated carbon (B), and coconut shell activated carbon (Cocos nucifera) (C). The type of adsorbent was AB, AC, and BC with ratio of 1:1, 1:2, 1:3, 2:1, and 3:1. The MB concentration was analyzed by using UV-Vis spectrophotometer. Isotherm adsorption was calculated based on Freundlich and Langmuir. The best results showed that the combination of fresh and regenerated betel nuts (AB) with ratio of 3:1 can remove 97.77% of MB. The adsorption process of MB in aqueous solution followed the Langmuir model with regression over 0.99 and adsorption capacity in the range of 2.14 mg/g - 3.53 mg/g.